2012
DOI: 10.5430/ijba.v3n5p52
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Service Quality Dimensions: An Empirical Analysis of Thai Hotel Industry

Abstract: The aim of this study is to focus on hotel service quality based on the application of 29 characteristic indicators from the SERVQUAL model by comparing two hotel types, namely the boutique and the business hotel, in Thailand and to understand the expectation, perception and gaps between expectation and perception regarding hotel service quality. The study applied a self-administered questionnaire to measure the expectation and perception of service quality characteristics of hotels in Thailand. A total of 108… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 35 publications
1
8
0
3
Order By: Relevance
“…Moreover, there have been numerous empirical studies supporting for the validity of the SERVQUAl model in the hotel service industry (Wilkins et al, 2007;Ladhari, 2009). These study adapted SERVQUAL scale with some modifications to measure hotel service quality such as Tsang and Qu (2000), Al Khattab & Aldehayyat (2011), Boonitt & Rompho (2012), Karunaratne & Jayawardena (2010), Juwaheer & Ross (2003). Moreover, there are studies which not only apply SERVQUAL to measure hotel service quality, but also use this measurement to investigate the impact of service quality on customer satisfaction such as Hossain (2012), Markovic & Raspor (2010), Juwaheer (2004.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, there have been numerous empirical studies supporting for the validity of the SERVQUAl model in the hotel service industry (Wilkins et al, 2007;Ladhari, 2009). These study adapted SERVQUAL scale with some modifications to measure hotel service quality such as Tsang and Qu (2000), Al Khattab & Aldehayyat (2011), Boonitt & Rompho (2012), Karunaratne & Jayawardena (2010), Juwaheer & Ross (2003). Moreover, there are studies which not only apply SERVQUAL to measure hotel service quality, but also use this measurement to investigate the impact of service quality on customer satisfaction such as Hossain (2012), Markovic & Raspor (2010), Juwaheer (2004.…”
Section: Literature Reviewmentioning
confidence: 99%
“…SERVQUAL scale (Parasuraman et al, 1988) is one of the most widely used instruments to measure service quality in various service fields including hotel business (Hossain, 2012;Boonitt & Rompho, 2012;Al Khattab & Aldehayyat, 2011). This study adopted SERVQUAL scale with some customizations to measure perceived service quality as well as examine the relationship between service quality and customer satisfaction in Vietnamese hotels.…”
Section: Analytical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, hospitality organizations have increasingly come to recognize the growing importance of service quality (Ford et al, 2012). That is, growing competition and increasingly demanding customers, as well as recessionary and globalization pressures, have emphasized the need for tourism and hospitality businesses to focus on improving service quality in order to achieve competitive advantage (Boon-itt and Rompho, 2012;Ramanathan and Ramanathan, 2011). Earlier, Lev (2001) suggested that the organization"s human systems should be thought of as one of its main competitive advantages.…”
Section: Literaturementioning
confidence: 99%